Missense variants in CTNNB1 can be associated with vitreoretinopathy—Seven new cases of CTNNB1‐associated neurodevelopmental disorder including a previously unreported retinal phenotype. Issue 1 (22nd December 2020) - Rossetti, Linda Z.; Bekheirnia, Mir Reza; Lewis, Andrea M.; Mefford, Heather C.; Golden‐Grant, Katie; Tarczy‐Hornoch, Kristina; Briere, Lauren C.; Sweetser, David A.; Walker, Melissa A.; Kravets, Elijah; Stevenson, David A.; Bruenner, Georgette; et al.
Abstract: Background: CTNNB1 (MIM 116806) encodes beta‐catenin, an adherens junction protein that supports the integrity between layers of epithelial tissue and mediates intercellular signaling. Recently, various heterozygous germline variants in CTNNB1 have been associated with human disease, including neurodevelopmental disorder with spastic diplegia and visual defects (MIM 615075) as well as isolated familial exudative vitreoretinopathy without developmental delays or other organ system involvement (MIM 617572). From over 40 previously reported patients with CTNNB1 ‐related neurodevelopmental disorder, many have had ocular anomalies including strabismus, hyperopia, and astigmatism. More recently, multiple reports indicate that these abnormalities are associated with the presence of vitreoretinopathy. Methods: We gathered a cohort of three patients with CTNNB1 ‐related neurodevelopmental disorder, recruited from both our own clinic and referred from outside providers. We then searched for a clinical database comprised of over 12, 000 exome sequencing studies to identify and recruit four additional patients. Results: Here, we report seven new cases of CTNNB1 ‐related neurodevelopmental disorder, all harboring de novo variants, six of which were previously unreported. All patients but one presented with a spectrum of ocular abnormalities and one patient, who was found to carry a missense variant in CTNNB1, had notable vitreoretinopathy. Conclusions: Our findings suggest ophthalmologic screening should be performed in all patients with CTNNB1 variants. Abstract : Here, we report seven new cases of CTNNB1 ‐related neurodevelopmental disorder, all harboring de novo variants, six of which were previously unreported. All patients but one presented with a spectrum of ocular abnormalities and one patient, who was found to carry a missense variant in CTNNB1, had notable vitreoretinopathy. Our findings suggest that ophthalmologic screening should be performed in all patients with CTNNB1 variants.